ANALISIS SEKTOR UNGGULAN DAN POTENSI PERTUMBUHAN EKONOMI SEBAGAI BASIS PERENCANAAN PEMBANGUNAN DAERAH DI KABUPATEN JEMBRANA - Ni Kadek Tasya Novita Devi; I Putu Gede Abdi Sudiatmika; A.A Raka Jayaningsih; I Made Wirayudha Jayendra; Ida Ayu Lalita Rathintara (STEKOM PRESS, 2024)
The aim of this research is to determine the leading sectors and potential for economic growth as a basis for regional development planning in the Jembrana Regency. The data used in this research is secondary data in the form of GRDP at constant prices, population, and per capita income for Bali Province and districts/cities, obtained from the Bali Province Central Statistics Agency (BPS) and Jembrana Regency BPS for the 2019-2023 period. This research uses a descriptive quantitative approach with five analytical techniques, namely techniques Location Quotient (LQ), Dynamic Location Quotient (DLQ), Growth Ratio Model analysis, and Overlay analysis. The research results show (1) five basic sectors, namely agriculture, forestry and fisheries, wholesale and retail trade; car repair; and motorbikes, the transportation and warehousing sector, the information and communications sector, and the real estate sector at 1.09. Based on the results of the Overlay analysis, 3 potential sectors in Jemebrana Regency have good growth and comparative advantages, including Agriculture, Forestry, and Jembrana Fisheries; Wholesale and retail trade; car repair; and motorbikes; Information and communication. (2) The results of the Growth Ratio Model analysis show that the agriculture, forestry, and fisheries sectors are sectors that have the potential to be developed in Jembrana Regency and have main development priorities